Chitosan Stabilized Multi-Walled Carbon Nanotubes for Electrochemical Determination of Dihydroxybenzene Isomers. Issue 13 (31st October 2017) - Kokulnathan, Thangavelu; Raja, Nehru; Chen, Shen-Ming; Sukanya, Ramaraj; Thirumalraj, Balamurugan
Abstract : We report a novel electrochemical sensor for the determination of dihydroxybenzene isomers using a chitosan (CS)-stabilized multiwalled carbon nanotube ( f -MWCNT)-modified electrode. The CS/ f -MWCNT composite was characterized by various physiochemical techniques and discussed in details. The CS/ f -MWCNT-modified electrode shows an excellent electrocatalytic activity towards the simultaneous detection of hydroquinone (HQ), catechol (CC) and resorcinol (RC) due to the active amino and hydroxyl functional groups of CS and f -MWCNT. In addition, the CS/ f -MWCNT-modified electrode exhibits wide linear response ranges for HQ, CC and RC concentrations of 0.09–171.4 μM, 0.09–155.43 μM and 0.3–174.82 μM, respectively. In addition, the CS/ f -MWCNT-modified electrode also achieved a lower detection limit (LOD) of 0.027 μM, 0.029 μM and 0.11 μM for HQ, CC and RC, respectively. Moreover, the practical applicability of the CS/ f -MWCNT-modified electrode can be applied for the determination of HQ, CC and RC in different water samples, and it exhibits satisfactory recovery and RSD values.